Cytogenetic analyses in 81 patients with brain gliomas: correlation with clinical outcome and morphological data - Kramář, Filip; Zemanová, Zuzana; Michalová, Kyra; Babická, Libuše; Ransdorfová, Šárka; Hrabal, Petr; Kozler, Petr (Journal of neuro-oncology, 2007)
Specific gene mutations, loss of heterozygosity, deletions and/or amplifications of entire chromosomal regions and gene silencing have been described in gliomas. 82 samples from 81 patients were investigated to detect the deletion of TP53, RB1, CDKN2A genes, deletion of 1p36 and 19q13.3 region, amplification of EGFR gene, trisomy of chromosome 7 and monosomy of chromosome 10 in glial cells. Dual-colour interphase fluorescence in situ hybridization (I-FISH) with locus-specific and/or chromosome enumeration DNA probes were used for cytogenetic analyses. In the study, molecular cytogenetic analyses were successfully performed in 74 patients (91.3%) and were uninformative in 7 only (8.7%). The cytogenetic analyses were correlated with morphological data and clinical outcome. I-FISH was the essential part of diagnostics. In comparison with the clinical data, the patients' age seems to be a factor more important for the overall survival, rather than cytogenetic findings in glial tumours. The combined deletion of 1p36 and 19q13.3 chromosomal regions predicts longer overall survival for patients with oligodendroglial tumours.
Keywords: financování organizované; dospělí; gliom; Female; Adult; ženské pohlaví; cytogenetické vyšetření; Adolescent; nádory mozku; lidé; Cytogenetic Analysis; Glioma; prognóza; Financing, Organized; Male; Aged; Brain Neoplasms; Prognosis; hybridizace in situ fluorescenční; lidé středního věku; senioři; mužské pohlaví; In Situ Hybridization, Fluorescence; Middle Aged; mladiství; Humans